Amalan Taqsim dalam permainan gambus Melayu di Johor: Kajian kes Maqamat / Raja Zulkarnain Raja Mohd Yusof - Raja Zulkarnain , Raja Mohd Yusof (2017)
This thesis will organize an academic study of the taqsim practice in the Malay gambus performance in Johor. The research focus on the analysis of the playing style and technique in gambus taqsim practice, and how a proper method and knowledge will manage to improve skills of the gambus players in Malaysia in performing the Malay songs especially from Johor. This research analyse the taqsim performance style with the Arabic identity of the gambus playing in Johor. This can be achieving after an observation from the selected gambus players in Johor. Taqsim (improvisation) that played during the opening; muqadimah in Arabic have two different forms, Taqsim (singular) and Taqasim (plural) contains a combination of various types of maqamat (Arabic modes) for use in the taqsim practice. This research examined the use of the maqamat in taqsim gambus practice which focused on the same harmony of the song being played by using a transcribing method of the taqsim perform by selected gambus players in Johor. Each maqamat distinguished from one Ajnas (maqam building blocks: Tri-chords, Tetra-chords and Penta-chords) to another sets of Ajnas and the western music notation system will be used in this study.